Simultaneous placement of short implants (≤ 8 mm) versus standard length implants (≥ 10 mm) after sinus floor elevation in atrophic posterior maxillae: a systematic review and meta-analysis - Chenxi Tang; Qianhui Du; Jiaying Luo; Lin Peng (SpringerOpen, 2022)
Abstract Purpose The objective of this meta-analysis was to compare the clinical outcomes of using short implants (≤ 8 mm) inserted with osteotome sinus floor elevation (OSFE) and standard implants (≥ 10 mm) inserted with sinus floor elevation (SFE) in atrophic posterior maxillae with insufficient residual bone height (RBH). Methods An electronic search was performed on PubMed, EMBASE, and the Cochrane Library from 1994 to July 2022, in combination with a manual search of references in relevant articles. Randomized controlled trials (RCTs) that compared the clinical results between short and standard implant placement with SFE were included. The primary outcomes were implant survival rate and marginal bone loss (MBL); the secondary outcome was complication rate. Results Three RCTs were included, totaling 138 short and 156 standard implants. The results of the meta-analysis showed no significant differences between the short and standard implant groups in survival rate (RR = 1.02, 95% CI   0.96-1.08, p = 0.570), MBL (MD = − 0.13, 95% CI   − 0.32 to 0.07, p = 0.190) and complication rate (intra-surgical complication: RR = 1.14, 95% CI   0.46-2.83, p = 0.770; post-operative complication: RR = 1.34, 95% CI   0.71-2.55, p = 0.370). Conclusions Using short implants (≤ 8 mm) combined with OSFE might be an alternative to standard implants (≥ 10 mm) with SFE when the RBH of the posterior maxilla is insufficient. Based on a short-term clinical observation, short implants with OSFE show good results in terms of survival rate, MBL, and complication incidence. Graphical Abstract